Photoactivatable prodrugs of butyric acid based on new coumarin fused oxazole heterocycles - Soares, Ana M. S. (2017)
New coumarin fused oxazoles were investigated as photosensitive units for carboxylic acid groups using butyric acid as a model compound. 6-Oxo-6H-benzopyrano[6,7-d]oxazol-8-yl)methyl derivatives possessing various (hetero)aromatic substituents at position 2 of the heterocyclic system were used in the synthesis of ester conjugates of butyric acid. Photolysis at selected wavelengths in methanol/HEPES buffer (80:20) solutions, monitored by HPLC/UV and 1H NMR, produced the complete release of butyric acid. The shorter irradiation times for cleavage at longer wavelengths occurred for the conjugate with a 4-oxo-4H-benzopyran-2-yl substituent and thus (6-oxo-2-(4-oxo-4H-benzopyran-2-yl)-6H-benzopyrano[6,7-d]oxazol-8-yl)methyl has potential as a candidate photosensitive moiety for butyric acid prodrugs.